Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1152/ajpendo.90314.2008
|View full text |Cite
|
Sign up to set email alerts
|

Leucine stimulates protein synthesis in skeletal muscle of neonatal pigs by enhancing mTORC1 activation

Abstract: Skeletal muscle in the neonate grows at a rapid rate due in part to an enhanced sensitivity to the postprandial rise in amino acids, particularly leucine. To elucidate the molecular mechanism by which leucine stimulates protein synthesis in neonatal muscle, overnight-fasted 7-day-old piglets were treated with rapamycin [an inhibitor of mammalian target of rapamycin (mTOR) complex (mTORC)1] for 1 h and then infused with leucine for 1 h. Fractional rates of protein synthesis and activation of signaling component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 39 publications
11
134
1
1
Order By: Relevance
“…Similarly, we could not detect any elevated phosphorylation by feeding (Fig. 6, E and F), although Akt-Ser 473 by any means is known to be highly sensitive to feeding (35,56,90). Recently, it was demonstrated that a threshold of insulin/amino acid availability has to be obtained for Akt to be phosphorylated (44,45), which may not have been obtained by the intermittent feeding regimen (Tables 2 and 3).…”
Section: Feeding and Exercise Signalingmentioning
confidence: 55%
“…Similarly, we could not detect any elevated phosphorylation by feeding (Fig. 6, E and F), although Akt-Ser 473 by any means is known to be highly sensitive to feeding (35,56,90). Recently, it was demonstrated that a threshold of insulin/amino acid availability has to be obtained for Akt to be phosphorylated (44,45), which may not have been obtained by the intermittent feeding regimen (Tables 2 and 3).…”
Section: Feeding and Exercise Signalingmentioning
confidence: 55%
“…WT or Pompe mice were fasted for 12 h and infused through an intravenous line with saline or leucine (30 mg·kg Ϫ1 ·min Ϫ1 ) for 1 h, then intraperitoneally injected with 1 U/kg insulin or saline for 30 min. These timeframes were chosen on the basis of previous studies examining insulin-and leucine-stimulated mTORC1 activation in skeletal muscle (24). Skeletal muscle was collected, snap-frozen, and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…One reason may be related to the premise of an important parameter for ruminants, according to Jorge et al (2008), which is the nutritional value of mesquite pod meal, that is, good bromatological composition, with a CP content of 9.4% and TDN higher than 70%, in addition to high DM digestibility. Suryawan et al (2008) reported that mesquite pod meal has a higher proportion of leucine when compared to corn, an essential amino that is at the heart of muscle protein synthesis. Moraes et al (2016) argued that the digestibility of nutrients was not affected by the replacement of corn for mesquite pod meal.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, it is worth highlighting the role of branched-chain amino acids (leucine, isoleucine and valine), with leucine being one of the main stimulators of protein synthesis in skeletal muscles (Suryawan et al, 2008), whose concentration in the mesquite pod accounts for 4.59% of all present amino acids (Zavala & González, 1997), concentration higher than that found in corn, of approximately 1.05%, based on dry matter (Agustini et al, 2015), as it is able to stimulate protein synthesis (Suryawan et al, 2008) and, when combined, boosts the increase in muscle growth through this amino acid (Wu, 2009). …”
Section: The Results Described Inmentioning
confidence: 99%